مکی دورِ نبوی ﷺ کے تہذیبی اثرات کا تجزیاتی مطالعہ: Analytical study of the cultural effects of the Meccan period of the Prophet ﷺ - Dr. Sajjad Ahmed; Ghulam Mustafa (Seerat Studies, 2023)
In order to mobilize and transfer his feelings and values, man first settled those places where the climate is moderate. Thus, man adopted a social form in a moderate place for his civilization and culture. Protection from natural disasters and the foundation of society was necessary for human nature. The position of a human being in society is that of a responsible person. The region of Makkah has always been a spiritual, religious and business center. During His period, the position of the Prophet Muhammad (peace be upon him) in Makkah was that of a distributer who benefited the people religiously and worldly. Jahili culture pushed human life into narrow and dark paths. Religion had been erased from the human mind and thought. On the arrival of Hazrat Muhammad ﷺ, this region was completely changed. Human thoughts changed. Civilization was pushed in a new and straight direction. Makkah remained the center of civilizations. The Prophet ﷺ brought a revolution by changing the self-made laws and rules of the people according to the requirements of the situation. With this change, the correct teachings maintained their place. However, the myths and the material against the interests of humanity were completely erased. Human civilization and culture were embellished with these changes, modifications, additions and refinements.